2012
DOI: 10.1128/jcm.06022-11
|View full text |Cite
|
Sign up to set email alerts
|

Baseline Cellular HIV DNA Load Predicts HIV DNA Decline and Residual HIV Plasma Levels during Effective Antiretroviral Therapy

Abstract: Cellular human immunodeficiency virus type 1 (HIV-1) DNA may be considered a marker of disease progression with significant predictive power, but published data on its correlation with plasma HIV RNA levels and CD4 counts in acute and chronic patients are not conclusive. We evaluated a cohort of 180 patients naïve for antiretroviral therapy before the beginning of treatment and after a virological response in order to define the indicators correlated with HIV DNA load decrease until undetectability. The follow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
30
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(41 citation statements)
references
References 29 publications
11
30
0
Order By: Relevance
“…This was confirmed by Parisi et al, who showed that baseline HIV DNA load predicted the residual HIV RNA plasma level during effective cART (107).…”
Section: Other Tissues and Fluidssupporting
confidence: 72%
See 3 more Smart Citations
“…This was confirmed by Parisi et al, who showed that baseline HIV DNA load predicted the residual HIV RNA plasma level during effective cART (107).…”
Section: Other Tissues and Fluidssupporting
confidence: 72%
“…The lowest HIV DNA levels were observed in patients who had low baseline levels and who received early treatment (107). In children, the HIV DNA level was markedly lower when viral control was achieved before age 1 year than between the ages of 1 and 5 years or after age 5 years (73).…”
Section: Time From Hiv-1 Infection To Treatment Initiation Influencesmentioning
confidence: 94%
See 2 more Smart Citations
“…A few data concerning long-term human immunodeficiency virus (HIV)-DNA monitoring have been reported [1][2][3][4][5][6][7] and it is not known how the demonstrated correlations between HIV-DNA levels and the main viro-immunological parameters could change over the course of effective treatment. The purpose of our study was to determine correlations between baseline HIV-RNA, cellular HIV-DNA, undetectable residual viremia (URV, <2.5 copies/mL), CD4 count, and acute or chronic infection at the start of antiretroviral therapy (ART) in naïve patients who responded to ART.…”
Section: Introductionmentioning
confidence: 99%